QiShenYiQi Pill Improves Myocardial Hypertrophy Caused by Pressure Overload in Rats. (17th June 2021) - Lv, Shichao; Wang, Qiang; Wu, Meifang; Li, Meng; Wang, Xiaojing; Xu, Ling; Zhang, Junping
Abstract : Pressure-overloaded myocardial hypertrophy is an independent risk factor for various cardiovascular diseases (CVDs), such as heart failure (HF), arrhythmia, and even sudden death. It is reported that QiShenYiQi pill (QSYQ) is widely used in the treatment of CVDs and can prevent pathological hypertrophy of myocardium, but its specific mechanism is still unclear. In this study, a rat model of myocardial hypertrophy was established through the pressure overload caused by abdominal aortic constriction in Wistar rats. The rats were randomly divided into model group, valsartan group, and QSYQ group, and sham-operated animals served as the control group. At the 4 and 8 weeks of intervention, the general morphology of the heart, myocardial collagen content, collagen volume factor (CVF), collagen type I, collagen type III, myocardial pathological changes, and the expression of ANP, β -MHC, TGF- β 1, and CTGF were analyzed, respectively, in order to explore the possible effect of QSYQ on the mechanism of myocardial hypertrophy. We observed that QSYQ could effectively improve myocardial hypertrophy in pressure-overloaded rats, which was related to the regulatory mechanism of TGF- β 1 and CTGF.